2019
DOI: 10.1186/s12905-019-0811-5
|View full text |Cite
|
Sign up to set email alerts
|

Health care informational challenges for women diagnosed with cervical intraepithelial neoplasia: a qualitative study

Abstract: Background Internationally, women with cervical intraepithelial neoplasia (CIN) lack knowledge about their disease, which limits their ability to take responsibility for self-care and creates negative psychosocial effects, including marital problems. Normally, screening is performed in primary care, and in case of abnormal results, the patient is referred to specialized care for follow-up and treatment. Given the lack of international literature regarding patients’ experiences in primary and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Service coordination among different levels of care was addressed in another study [ 27 ]. In our study, since the most women interviewed had visited at least three doctors, Iranian physicians should follow a multidisciplinary approach and, knowing their own limitations, refer patients to proper specialist facilities as a first step towards effective management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service coordination among different levels of care was addressed in another study [ 27 ]. In our study, since the most women interviewed had visited at least three doctors, Iranian physicians should follow a multidisciplinary approach and, knowing their own limitations, refer patients to proper specialist facilities as a first step towards effective management.…”
Section: Discussionmentioning
confidence: 99%
“…A research has shown informational challenges and communication gaps occurred for women diagnosed with CIN in the moments of the CC screening in primary care, waiting time until referral to specialized care, first consultation in specialized care, and after consultation in specialized care [ 27 ]. Relatively little research has also shown that healthcare providers have knowledge gaps [ 28 ] and there is no adequate flow of HPV-related information between HCPs and women [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous publications derived from this study have focused on exploring the experiences of women during medical surveillance for CIN [15,26]. The results showed that women who have a diagnosis of CIN experienced important healthcare informational challenges when accessing primary and specialised care, which had several repercussions on their wellbeing.…”
Section: Introductionmentioning
confidence: 90%
“…The results showed that women who have a diagnosis of CIN experienced important healthcare informational challenges when accessing primary and specialised care, which had several repercussions on their wellbeing. The dearth of information provided and women's limited knowledge about HPV infection and treatment made it difficult for them to understand and participate in decision-making about CIN prevention and treatment [15]. Additionally, we revealed how patients' daily lives were affected by risk management in CIN medical surveillance [26].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation